PERSEPSI PASIEN RAWAT INAP KLAS III TERHADAP RESPONSIVENESS PELAYANAN DOKTER DAN PERAWAT DI RUMAH SAKIT UMUM DAERAH RAA SOEWONDO PATI - Nydia Veramita; Anneke Suparwati; Putri Asmita Wigati (Jurnal Kesehatan Masyarakat (Undip), 2016)
Responsiveness is non-medical aspects of how a person is treated. This study was conducted to determine the perception of hospitalized patients class III to reactivity doctors and nurses service were seen on 3 domain ie friendliness agent responsiveness, clarity of information, and long periods of expectation. This research is opservasional. The population in this study were all hospitalized patients class III hospitals RAA Soewondo Pati. The sample of this research is 73 respondents. The sampling technique using simple random sampling formulas. Data collection methods using questionnaires and structured documentation. The data analysis of this research is the analysis of univariate. Univariate analysis was to describe all the variables of the study. The results of this study dilhat of two factors, namely higher education and vocational education is getting to know the quality of health services. For the perception of the responsiveness of service doctors and nurses patient were seen on 3 domain ie friendliness agent responsiveness, clarity of information, and the long period of waiting, the results of responsiveness care physician All patients responded to 100% friendly doctor, nurse showed all patients also answered 100% friendly and for the clarity of the information, there are still 19.2% of which are not agreed to answer questions relating to an easily understandable explanation of the patient's condition is considered, and the last for this long wait almost all patients respond in accordance with the highest value of 93.2% to a question Related responsiveness of nurses and doctors in emergency conditions. Doctors and nurses reactivity was good, both in normal and in emergency situations. Both have received a positive response from respondents. But doctors and nurses need to improve their communication skills, as there are still some respondents are not always able to understand their explanation.